(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The paper presents the methods of exponential functions and differential equations recommended by IEC and IEEE for the calculation of the oil θo and hot spot θh temperatures in power transformers, in the absence and presence of solar radiation. Considering the case of distribution transformers, for which the load factor K shows variations in small time intervals, the authors propose a new (analytical) method for calculating temperatures (θo and θh), both in the absence and in the presence of solar radiation. To highlight the importance of the calculation method and solar radiation, the quantities θo and θh are calculated (in two days from 2019) by three methods, as well as the consumed and remaining lifetimes for two transformers, with the same load and located in areas with different values of temperature and solar radiation. Finally, the influence of solar radiation, place of operation of the transformer, and calculation method on the values of temperatures and lifetimes are analyzed.